2014
DOI: 10.2147/ndt.s67668
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12, folate, and homocysteine levels in patients with obsessive–compulsive disorder

Abstract: It is known that elevated serum homocysteine, decreased folate, and low vitamin B12 serum levels are associated with poor cognitive function, cognitive decline, and dementia. Current literature shows that some psychiatric disorders, mainly affective and psychotic ones, can be related to the levels of vitamin B12, folate, and homocysteine. These results can be explained by the importance of vitamin B12, folate, and homocysteine in carbon transfer metabolism (methylation), which is required for the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Similarly, Türksoy et al . 25 reported that patients with obsessive–compulsive disorder might have higher homocysteine levels; however, the patient and control groups predominantly comprised female patients (88.6% and 86.4%, respectively). One possible mechanism underlying the link between homocysteine and anxiety may be related to brain oxidative status.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Türksoy et al . 25 reported that patients with obsessive–compulsive disorder might have higher homocysteine levels; however, the patient and control groups predominantly comprised female patients (88.6% and 86.4%, respectively). One possible mechanism underlying the link between homocysteine and anxiety may be related to brain oxidative status.…”
Section: Discussionmentioning
confidence: 98%
“…In case of deficiencies, there is a decrease in re-methylation of homocysteine, which leads to an increase in homocysteine level 6. Reflecting their importance in CNS metabolism, previous studies reported that deficiencies in vitamin B12 and folate levels, as well as changes in homocysteine, might be related with depression, mood disorders, psychotic disorders, an obsessive-compulsive disorder 79. Recently, some studies have reported deficiencies in the levels of vitamins B12 and folate (vitamin B9) in patients diagnosed with ASD and ADHD as well as beneficial effects of those vitamins for some of the associated ASD and ADHD symptoms 1012.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in our study vitamin B12 was found lower in concentration, 208.14 (P=0.004) in cases of 44 patients (test group) as compared to control group. [13] There are few cases available in literature in which vitamin B12 deficiency has been directly found associated with clinical depression. In one such case reported by Durand C of a patient with vitamin B12 deficiency, who presented severe depression with delusion and Capgras' syndrome, delusion with lability of mood and hypomania successively, during a period of two Months.…”
Section: Discussionmentioning
confidence: 99%